Analysis of the Effectiveness of Learning Multimedia Based on Contextual Learning in Elementary Schools - Agung Wibowo; Anita Yus; Deny Setiawan (PT FORMOSA CENDEKIA GLOBAL, 2022)
Science is one of the main subjects that must be taught in schools. Elementary school students think science learning materials are difficult, boring, and even scary. Media is needed to connect material with real student activities. So the researchers analyzed contextual-based multimedia. This research is a descriptive study with a literature review and field observations. The results showed that the fifth grade teachers at SDN 250 Sinar Gading II used multimedia presentations and effectively increased student learning outcomes with an average score of 73 and 88. The results showed that multimedia was effective in improving student learning outcomes.